The age-specific pathological changes of β-amyloid plaques in the cortex and hippocampus of APP/PS1 transgenic AD mice. (2nd December 2022) - Xue, Lu-Lu; Huangfu, Li-Ren; Du, Ruo-Lan; Chen, Li; Yu, Chang-Yin; Xiong, Liu-Lin; Wang, Ting-Hua
ABSTRACT: Objective: Numerous pathological variations and complex interactions are involved in the long period prior to cognitive decline in brains with Alzheimer's disease (AD). Thus, elucidation of the pathological disorders can facilitate early AD diagnosis. The aim of this study was to investigate the age-specific pathological changes of β-amyloid plaques in brain tissues of AD mice at different ages. Methods: We arranged the most widely available APP/PS1 transgenic AD models into six age groups: 3, 4 and 6 months (these three groups mimicked early-clinical stage AD), 9, 12 and 15 months (these three groups mimicked late-clinical stage AD). Cell morphology and arrangement in the cortex and hippocampus were observed by hematoxylin and eosin (HE) staining. Congo red staining and immunohistochemical staining were performed to exhibit the distribution of β-amyloid plaques in the cortex and hippocampus of AD brains. Results: Our results found that as age increased, the nuclei of cortical and hippocampal cells in AD mice were severely damaged. The number and area of β-amyloid plaques increased in AD mice in correspondence with age revealed by histological experiments. Importantly, β-amyloid plaques were detected in the cortex and hippocampus of 6-month-old AD mice shown by Congo red staining while detected in the cortex and hippocampus of 4-month-old AD mice shown by immunohistochemical staining. Conclusions: The current study revealed the age-related pathological changes of β-amyloid plaques in the cortex and hippocampus of AD mice and displayed a higher specificity of immunohistochemical staining than Congo red staining when detecting pathological changes of brain tissues.